Study of Antioxidant Activity in Rice Bran and Skim Milk Media Fermented by Probiotic (Lactobacillus plantarum B2 and Lactobacillus acidophillus) - Zubaidah, Elok; Saparianti, Ella; Hindrawan, Josep (Jurnal Teknologi Pertanian, 2012)
Many cereal-based functional food products have been developed nowadays including probiotic and prebiotic products. Rice bran as a by product of rice milling mostly consists of insoluble fibers and antioxidants thatpotential for functional food products such as lactic acid bacteria (LAB) fermented products. This research was aimed to evaluate the increase in bioavailability of antioxidant of LAB-fermented (probiotic) rice bran and skim milk as well as to identify the most effective isolate of LAB to increase antioxidant bioavailability. The randomized block design with two factors (fermentation substrate: rice bran 16% and skim milk 16%; isolates: L.plantarum B2 and L.acidophillus) was applied. The experiment was conducted with three replications. The results showed that the best treatment was L.plantarum B2-fermented rice bran with total LAB of 3.35x1010 cfu/mL, total acid of0.86%, pH of 4.13, insoluble fibers of 1.32%, total phenol of53.14 ppm, and antioxidant activity of of 86.41%. Keywords: rice bran, skim milk, probiotic, antioxidant activity